Educational intervention on oral cancer and its prevention in pre-university students - José Carlos Alvarez Hernández; Eniley Quintana Morales; Ailen Guzmán López; Marino Enrique León Palombí; Marileidi Morales Cabrera; Mara Isabel Morales Pardo (Medisur)
Foundation: the increase in the incidence of oral cancer constitutes a global health problem, there is a need to carry out educational actions that contribute to the prevention of the disease from an early age. Objective: to evaluate the effectiveness of an educational intervention on oral cancer and its prevention in students from a pre-university center. Methods: a pre-experimental educational intervention study was carried out, with a pre-test/post-test design, from November 2021 to May 2022. The entire universe was studied, 125 students from the Roberto Rodríguez School in Morón municipality, Ciego de Ávila. Descriptive and inferential statistics were used. Results: 52.0% of the participants were female. The mean age for both sexes was 15.86 ± 1.053 years. 36.8% were in eleventh grade. Inadequate levels of information were determined in the diagnostic stage in terms of: generalities (96.0%), risk factors (91.2%), oral self-examination (96.0%) and promotion and prevention measures (95.2%). %). After applying the intervention, the cognitive level was raised to 97.6%, 99.2%, 96.8% and 99.2% respectively. The McNemar test showed significant results (p = 0.000; p < 0.05). Conclusions: a statistically significant modification of the information was achieved in each of the respondents, so it could be inferred that the educational intervention was effective.